Policy on Academic Management Information System in Madrasahs - Ahla Firdausi, Rizqi (UIN Sunan Gunung Djati Bandung, 2024)
Academic Management Information System (SIMAK) is an information system used to present information and organise administration related to academic activities in schools or the world of schooling, so that schools can provide good and effective information services. The purpose of SIMAK design is to provide information about periodic test scores, KTSP data, KBK score data, attendance data, guidance and counselling data, student case data, teaching plans, subject management, scheduling, and academic achievement. In Indonesian, Software Engineering is known as the term Software Engineering (RPL). Problems in implementing the SIMAK model in general terms are the same as problems in managing information management systems in general